Wyposażenie i efektywność środków trwałych w gospodarstwach indywidualnych o różnych typach produkcyjnych - Wasilewska, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The paper presents changes of equipment and efficiency of fixed assets in relation to the financial outcomes of farms classified to various production types. The statistical base for the above analysis was the data from FADN system. Therefore analysed sample of farms was representative in aspect of production types in Poland. The research concerned farms which sold their production on the market. In this context the outcomes of analysis could lead to the improvements of farms’ organization in various types.